Oral Health Impact Profile in Celiac Patients: Analysis of Recent Findings in a Literature Review - Gabriele Cervino; Luca Fiorillo; Luigi Laino; Alan Scott Herford; Floriana Lauritano; Giuseppe Lo Giudice; Fausto Famà; Rossella Santoro; Giuseppe Troiano; Gaetano Iannello; Marco Cicciù (Gastroenterology Research and Practice)
The increment of recording atypical oral manifestation in young patients often related to systematic disease is today a challenge for the therapists. Sometime, the presence of tooth enamel lesions correlated with soft tissue lesions is just a symptom or a trigger sign for a deeper and undetermined disease. Recently, high impact has been developed toward the influence of the diet as a controlled and modifiable factor in patients affected by celiac pathologies. The celiac disease (CD) is a chronic immune-mediated disorder triggered by the ingestion of gluten that appears in genetically predisposed patients. Gluten is a proline-rich and glutamine-rich protein present in wheat (gliadin), barley (hordein), and rye (secalin). The gluten-free diet (GFD) seems to better influence the oral health status of the CD patients. For this reason, the main objective of this revision was to analyze the international data highlighting the relationship between celiac patients and the oral health impact profile. A comprehensive review of the current literature was conducted according to the PRISMA guidelines by accessing the NCBI PubMed database. Authors conducted the search of articles in the English language published from 2008 to 2018. The first analysis with filters recorded 67 manuscripts accordingly with the selected keywords. Finally, a number of 16 appropriate published papers were comprehended in the review. The studies were different in terms of the structure, findings, outcomes, and diet quality evaluation, and for this reason, it was not possible to accomplish a meta-analysis of the recorded data. This manuscript offers some observational evidence to justify the advantages of gluten-free diets related to a better oral health status in the patients involved.